Implementation of Green Supply Chain Management Practices in Zimbabwean Organizations - Cynthia Mupfiga; Munyaradzi Chibaro; Munyaradzi Mahwine; Munyaradzi Muchemwa (Research Synergy Press, 2024)
The study looked into the implementation of green supply chain management practices in Zimbabwean Organizations. Since 2000, Zimbabwe has witnessed a significant number of business closures, which has consequently impeded the adoption of green supply chain practices. The study was guided by the objectives that included investigating the need to implement green supply chain management, examining implementation success factors that promote green supply chain management, and identifying the challenges faced in promoting green supply chain management. Interpretivism research philosophy and descriptive research design were adopted in this study. A specific population was drawn from 150 employees of selected Zimbabwean logistic companies. Non-probability sampling methods were adopted in this study. The findings on climate concern as the need for green supply chain implementation show that 10% strongly disagree with that view, 35% were neutral, and the other 30% strongly agreed. Findings on green manufacturing technology practice as one of the success factors that promote green supply chain management showed that 15% strongly disagreed with the view, 30% were neutral, and the other 30% strongly agreed. The findings on regulatory challenges faced in promoting green supply chain management show that 10% strongly disagree with that view, 35% were neutral, while the other 30% strongly agreed. This study demonstrates that green supply chain management is crucial for environmental protection, mitigating pollution, and addressing climate-related challenges. It recommends that organizations and other stakeholders in Zimbabwe develop various strategies to enhance the implementation of green supply chain practices.